2015
DOI: 10.1002/2015gl066641
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry‐turbulence interactions and mesoscale variability influence the cleansing efficiency of the atmosphere

Abstract: The hydroxyl radical (OH) is the most important oxidant in the atmosphere and the primary sink for isoprene, the dominant volatile organic compound emitted by vegetation. Recent research on the atmospheric oxidation capacity in isoprene‐dominated environments has suggested missing radical sources leading to significant overestimation of the lifetime of isoprene. Here we report, for the first time, a comprehensive experimental budget of isoprene in the planetary boundary layer based on airborne flux measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 74 publications
2
71
2
Order By: Relevance
“…Hereafter we use the notation knormalefffalse[normalBVOC]¯(z) to represent the sum of the three terms inside square brackets in equation and define a time scale associated with the ozone loss in the oxidation of the BVOCs as τnormalchem(z)=1knormalefffalse[normalBVOC]¯(z). The intensity of segregation cannot be determined from the measurements available as this would require simultaneous, high‐frequency measurements of the two species involved. While the intensity of segregation between isoprene and OH may be significant [e.g., Kaser et al , ], the reactivity between ozone and terpenes is much lower (due to the much lower ambient levels of terpenes compared to isoprene) and segregation effects are expected to be much smaller [e.g., see Ouwersloot et al , ]. These effects are neglected hereafter and the approximation knormal[A]normaleffknormal[A] is employed.…”
Section: Methodsmentioning
confidence: 99%
“…Hereafter we use the notation knormalefffalse[normalBVOC]¯(z) to represent the sum of the three terms inside square brackets in equation and define a time scale associated with the ozone loss in the oxidation of the BVOCs as τnormalchem(z)=1knormalefffalse[normalBVOC]¯(z). The intensity of segregation cannot be determined from the measurements available as this would require simultaneous, high‐frequency measurements of the two species involved. While the intensity of segregation between isoprene and OH may be significant [e.g., Kaser et al , ], the reactivity between ozone and terpenes is much lower (due to the much lower ambient levels of terpenes compared to isoprene) and segregation effects are expected to be much smaller [e.g., see Ouwersloot et al , ]. These effects are neglected hereafter and the approximation knormal[A]normaleffknormal[A] is employed.…”
Section: Methodsmentioning
confidence: 99%
“…Kaser et al . [] have recently shown that in addition to uncertainties in atmospheric chemistry schemes, the limited spatial resolution of models masks the true spatial covariability and spatial segregation of BVOC and atmospheric oxidants, which can result in up to 30% overestimation of isoprene oxidation rates. Figure depicts this process where two different air parcels over heterogeneous landscapes (cropland versus mixed oak forests) that are separated by a distance of just a few kilometers have very different concentrations of OH radicals and isoprene: one with high OH and low isoprene and the other with low OH and high isoprene.…”
Section: Biogenic Emissions and Soa Formationmentioning
confidence: 99%
“…For midday conditions, the chemical tendency of isoprene can be estimated following Reynolds decomposition as trueC5H8¯tchemistry=prefix−truek¯[]trueC5H8¯0.5emtruenormalOnormalH¯0.5emprefix+1emtrueC5H80.5emnormalOH¯, where k is the C 5 H 8 + OH reaction rate coefficient, the bars denote time and space averages, and the primes are deviations or fluctuations from the averages [e.g., Kaser et al ., ]. By discretizing the conservation equation on a grid, regional‐ and global‐scale models implicitly average over all motions smaller than the grid size.…”
Section: Introductionmentioning
confidence: 99%